Characterization and Rheological Behavior of Dextran from Weissella confusa R003 - Siwames Netsopa; Suwanna Niamsanit; Duangkamon Sakloetsakun; Nipa Milintawisamai (International Journal of Polymer Science)
Dextran from Weissella confusa R003 isolated from sugar cane juice was purified and characterized. Dextran synthesis was performed by fermenting W. confusa R003 in MRS medium containing 10% (w/v) sucrose with continuous shaking at 125 rpm and at 30°C. For 24 hours, the 50% efficiency yield was obtained. Dextran in the culture medium was purified by ethanol precipitation. Structural analysis of dextran using 1H NMR, 13C NMR, and 2D NMR techniques showed the existence of glucoses with 97.4%  α (1→6) linkage in the main chains and 2.6%  α (1→3) in branches. The estimation of molecular weight by dynamic light scattering exhibited average molecular weight of 1.0 × 104 kDa. At low concentration (2.5% w/v), dextran behaved like liquid structure, while, increasing the concentration (5.0 and 10.0% w/v), it was revealed as viscoelastic behavior. The highest gelling phenomenon was found in the concentration of 10% w/v and at 37°C. Due to its production and properties, it may be suitable for commercial production and application in the field of foods as well as hydrogel.